Prevalence of allergic rhinitis symptoms and associated factors in six-year-old children in a municipality in southern Brazil - Manuela Silva e Silva; Jefferson Traebert; Daniel José da Silva Filho; Eliane Traebert (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To estimate the prevalence of allergic rhinitis symptoms and associated factors in six-year-old children. Methods: Cross-sectional epidemiological study involving 956 six-year-old schoolchildren from Palhoça, Santa Catarina, Brazil. Home interviews were conducted with mothers in which socio-demographic and house environmental conditions information were obtained, and the International Study of Athma and Allergies in Childhood (ISAAC) questionnaire for allergic rhinitis symptoms was applied. Bivariate and multivariate hierarchical analyses were performed using Poisson regression with a robust estimator. Results: The prevalence of allergic rhinitis symptoms was 21.7%. Children whose mothers had over 8 years of education, or who had air conditioning equipment in the house, or whose bedroom walls presented mold or moisture showed statistically significant and independent 5% higher prevalence of allergic rhinitis. Similarly, children of smoker mothers or those who lived with fur or feather animals indoors showed a 4% higher prevalence. Conclusion: Significant associations were observed between socio-demographic factors and environmental conditions in child's home and allergic rhinitis symptoms in children aged six years.